2000
DOI: 10.1034/j.1600-051x.2000.027008597.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacteroides forsythus, Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans in subgingival microflora of Japanese patients with adult and rapidly progressive periodontitis

Abstract: The prevalence and the proportion of B. forsythus and P. gingivalis were significantly correlated with clinical parameters, suggesting that B. forsythus and P. gingivalis are closely related to AP and RPP in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 24 publications
6
70
1
1
Order By: Relevance
“…Several studies reported that major high molecular mass proteins larger than 200 kDa were characteristic of T. forsythensis (Kerosuo, 1988;Gersdorf et al, 1993). We have shown by immunoelectron microscopy that the S-layer is composed of 230 and 270 kDa major proteins (Higuchi et al, 2000;Moriguchi et al, 2003). These S-layer proteins were shown to be specifically recognized by sera from patients with periodontitis (Yoneda et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies reported that major high molecular mass proteins larger than 200 kDa were characteristic of T. forsythensis (Kerosuo, 1988;Gersdorf et al, 1993). We have shown by immunoelectron microscopy that the S-layer is composed of 230 and 270 kDa major proteins (Higuchi et al, 2000;Moriguchi et al, 2003). These S-layer proteins were shown to be specifically recognized by sera from patients with periodontitis (Yoneda et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies have suggested an aetiological role of this organism in several forms of periodontal disease (Gersdorf et al, 1993;Takemoto et al, 1997;Haffajee et al, 1998;Yano-Higuchi et al, 2000), periradicular lesion (Gonçalves & Mouton, 1999;Siqueira & Rô ças, 2003) and systemic disease (Noack et al, 2001;Hajishengallis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of this spectrum, possibly 10 to 20 species participate in the pathogenicity and periodontal destruction in periodontal disease 19 , with a prevalence of gram-negative anaerobic bacilli and among them, A. actinomycetemcomitans (Hacek group), P. gingivalis and P. intermedia, with a predominance in gingival samples 20 .…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] Although many factors may influence the onset of periodontitis, periodontopathogen bacteria play a key role in the onset and severity of periodontal diseases. [42,45,46] PG is an anaerob obligat, [47] non-motile, [48] pleiomorphic bacteria, and posses a capsul. [49] PG shows a strong proteolitic activity, grows in anaerobic environment, and shows dark pigmentation (brown, dark green, or black) on blood agar.…”
Section: Literature Reviewmentioning
confidence: 99%